REPLACING FISH MEAL WITH UNTREATED AND ENZYMATICALLY TREATED TORULA YEAST (CYBERLINDNERA JADINII) AFFECTS PELLETING DIE FLOW RESISTANCE AND PHYSICAL PROPERTIES OF THE FEED PELLETS - Miladinovic, Dejan Dragan (Food and Feed Research, 2026)
Yeast is gaining importance as a novel feed ingredient. Although fishmeal generally provides better feed conversion in farmed aquatic animals, research suggests that the torula yeast Cyberlindnera jadinii (CJ) is a promising alternative to fishmeal. This study examines the effects of replacing fishmeal with torula yeast (CJ), both untreated and treated with protease and endo-exo 1.3-beta-glucanase, on pellet production. The first experiment evaluated changes in flow resistance and pellet quality when fishmeal was replaced with yeast. The second experiment focused on how enzyme-treated yeast influenced these factors. Pellets containing 20% CJ, whether treated or not, showed increased flow resistance and higher pellet strength. Pellets formulated with 10% and 20% CJ, as well as pellets composed solely of yeast material used as a control, exhibited water-repellent properties, potentially enhancing feed intake, reducing waste, and supporting sustainable production. However, pellets with 10% and 20% enzyme-treated CJ showed fat-repellent behavior, which may hinder post-production processes. Enzymatic treatment reduced underwater swelling in these pellets, and minimal hydrolysis is recommended to limit disintegration. Enzyme treatment reduced surface roughness, with pellets containing 20% treated CJ exhibiting the smoothest texture.